Pengaruh Pemberian Ekstrak Biji Kopi Robusta (Coffea canephora) Lampung Terhadap Aktivitas Enzim Katalase Cerebellum Tikus Putih (Rattus norvegicus) Jantan Galur Sprague-dawley yang Diinduksi Monosodium Glutamate - Syifa Fakhirah Siregar; Anggraeni Janar Wulan; Dwita Oktaria (Medula, 2023)
Excessive consumption of monosodium glutamate (MSG) has a neurotoxic effect on the cerebellum, which will lead to a state of oxidative stress characterized by decreased activity of catalase. This study aims to determine the effect of Lampung Robusta Coffee extract (Coffea canephora) againsts to activity of the cerebellar catalase enzyme in male rats (Rattus norvegicus) strain sprague-dawley induced by monosodium glutamate. This research is a type of experimental study with a Posttest Only Control Group Design approach. The subjects were 25 rats which were divided into 5 groups which are K- (aquadest 3,5 ml/day), K+ (MSG 4 g/kgBW/day), P1, P2, P3 (MSG 4 g/kgBW/day and Lampung Robusta Coffee extract 1,5 ml/200gBW/day with a concentration of 0,03 g/ml; 0,06 g/ml; 0,12 g/ml respectively) for 14 consecutive days. The activity of the cerebellar catalase enzyme is calculated with spectrophotometer 210 nm. The average specific activity of the cerebellum catalase enzyme in K +, K-, P1, P2 and P3 were 0.00104 U/mg, 0.00154 U/mg, 0.00139 U/mg, 0.00161 U/mg, and 0.00190 U/mg respectively. One-Way ANOVA test obtained p value = 0.001 (p <0.05). Post Hoc LSD test showed a significant difference (p <0.05) between the K + and K- (p = 0.007), K+ and P2(p = 0.003), K + and P3 (p = 0.000), and P1 and P3 (p = 0.007), which means that there is an effect of Lampung Robusta Coffee extract (Coffea canephora) againsts to activity of the enzyme catalase of cerebellar in male rats (Rattus norvegicus) strain Sprague-dawley induced by MSG.